Posterior versus lateral surgical approach: functionality and quality of life after total hip arthroplasty in a matched cohort study - Davide Castioni (BMC, 2021)
Abstract Background One of the most controversial aspects for maximizing outcomes after total hip arthroplasty (THA) remains the surgical approach to the hip joint. The posterior (PA) and lateral approaches (LA) are the two most commonly performed approaches used worldwide, but sparse data are available for their comparison in terms of health-related quality-of-life (HRQoL). The aim of this study was to assess the role of the PA and LA in the HRQoL and hip functionality of patients who underwent primary and elective THA for osteoarthritis, after a minimum 2-year follow-up. Methods One hundred twenty-eight patients (140 THAs: 68 with PA and 72 with LA) were evaluated in a matched cohort study. Data gathered included the body mass index, the American Society of Anesthesiologists score, surgery time, serum creatine phosphokinase (CpK) levels, estimated intraoperative blood loss and intra- or postoperative complications. Preoperatively and at the last follow-up, the activities of daily living, and the instrumental activities of daily living (IADL) scales, the Western Ontario and Mac Master University (WOMAC) Questionnaire, the Harris Hip Score (HHS) and the Visual Analogue Scale (VAS) were used to assess HRQoL and functionality. The Short Form-36 Health Survey (SF-36) Questionnaire was administered at the last follow-up. Results Postoperatively, CpK was higher in the LA group compared to the PA (695 ± 648 vs. 447 ± 326 UI/L, p < 0.001). At a mean follow-up of 47 ± 22 months for the LA group and 42 ± 29 months for the PA group, IADL, VAS, HHS and WOMAC scores significantly improved for both groups (all p < 0.001), but PA reported better VAS, residual pain and WOMAC scores (p = 0.002, p = 0.004 and p = 0.018, respectively). The PA group demonstrated a significant higher mental SF-36 subscale values than the LA group (49 ± 13 vs. 42 ± 19, p = 0.001). The LA group showed a higher number of Trendelenburg signs (p = 0.029). On the contrary, the PA group showed a higher number of leg lengthening (p = 0.020); however, most of these cases was less than the clinically significant value of 10 mm (p = 0.738). Conclusions Patients who underwent THA performed with the PA reported greater improvement in HRQoL with lower residual pain, postoperative muscle damage and Trendelenburg signs than those who underwent the LA.